Update of Nanoparticle-Catalyzed Synthesis of Heterocyclic Scaffolds Reported in 2023 - Desai, Meet; Dhameliya, Tejas (Synlett, 2025)
With an urge to develop easy and affordable catalysts, the development of nanoparticles, which can be easily utilized in various synthetic procedures, has been the need of the hour. Over the last few decades, the use of nanoparticles has increased drastically because of their unique properties and easy recoverability and reusability. The synthesis of heterocyclic compounds has made extensive use of nanocatalysis due to the development of nanotechnology. Several organic transformations have been carried out using a variety of nanoparticles, which notably motivated us to report on the uses of metal nanoparticles in the production of heterocyclic scaffolds as was published in 2023. This article summarizes the use of nanoparticles in the synthesis of various nitrogen- and oxygen-containing heterocycles, their properties, recoverability, and reusability.
Keywords: Nanoparticles; Heterocycles; Nanocatalysis; Metal nanoparticles; Aza heterocycles; Oxa heterocycles